2016
DOI: 10.1590/1414-431x20155005
|View full text |Cite
|
Sign up to set email alerts
|

Microglia and neurons in the hippocampus of migratory sandpipers

Abstract: The semipalmated sandpiper Calidris pusilla and the spotted sandpiper Actitis macularia are long- and short-distance migrants, respectively. C. pusilla breeds in the sub-arctic and mid-arctic tundra of Canada and Alaska and winters on the north and east coasts of South America. A. macularia breeds in a broad distribution across most of North America from the treeline to the southern United States. It winters in the southern United States, and Central and South America. The autumn migration route of C. pusilla … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 35 publications
0
14
1
Order By: Relevance
“…The hippocampus seems to be essential in birds for recalling landmarks and migratory routes in long-distance navigation ( Mettke-Hofmann and Gwinner, 2003 ; Mouritsen et al, 2016 ). The involvement of the hippocampus in these tasks is reflected in the neuroanatomical differences between the hippocampal formation in migratory versus non-migratory bird species ( Krebs et al, 1989 ; Sherry and Vaccarino, 1989 ; Jacobs et al, 1990 ; Healy and Krebs, 1996 ; Garamszegi and Eens, 2004 ; Lucas et al, 2004 ; Roth and Pravosudov, 2009 ; LaDage et al, 2010 , 2011 ; Diniz C.G. et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The hippocampus seems to be essential in birds for recalling landmarks and migratory routes in long-distance navigation ( Mettke-Hofmann and Gwinner, 2003 ; Mouritsen et al, 2016 ). The involvement of the hippocampus in these tasks is reflected in the neuroanatomical differences between the hippocampal formation in migratory versus non-migratory bird species ( Krebs et al, 1989 ; Sherry and Vaccarino, 1989 ; Jacobs et al, 1990 ; Healy and Krebs, 1996 ; Garamszegi and Eens, 2004 ; Lucas et al, 2004 ; Roth and Pravosudov, 2009 ; LaDage et al, 2010 , 2011 ; Diniz C.G. et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…A recent study investigated two sandpiper species with contrasting demands on visuospatial learning during their migrations. One species, Actitis macularia , relies more on remembering visual cues during overland migration and has a larger hippocampus and more microglial cells than the other species, C. pusilla , which migrates via a long-distance non-stop flight over the Atlantic Ocean ( Diniz C.G. et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…The current study of the hippocampus region shows that it consists of two regions: which agrees with Belgard and Tompol (13) (14). When studying chicken and Homing pigeon, it consists of a network of nerve fibers as well as the presence of nerve cells (15). The study shows that two species of birds migrated long distances, such as the semipalmated sandpiper (Calidris pusilla), and the second migrated to short distances as spotted sandpiper (Actitis macularia).…”
Section: Discussionmentioning
confidence: 97%
“…The same study showed that hippocampal volume did not change in the resident Sardinian warbler. A recent study on two sandpiper species with different demands on visuospatial learning during migration also revealed a larger hippocampus and a larger number of microglia cells therein in the species with more demand on remembering visual cues during overland migration ( Actitis macularia ) as compared to Calidris pusilla with more non-stop flight over the Atlantic Ocean (Diniz et al 2016 ). Overall, migrants seem to have a better spatial memory as an adaptation to their to and fro migration than residents.…”
Section: Cognitive Abilities Of Birds With Different Movement Strategmentioning
confidence: 92%